(untitled) (The East and Central African Journal of Pharmaceutical Sciences, 2022)
Metronidazole benzoate is an ester derivative of metronidazole utilized in the formulation of oral suspensions owing to its palatability. The drug is liable to hydrolytic degradation during shelf life which could lower assay values and increase free metronidazole content. A medicine quality survey study was carried out in Nairobi County whereby 32 metronidazole benzoate samples representing 13 brands were collected from retail pharmacies. The samples were subjected to British Pharmacopoeia specifications for pH, free metronidazole content and assay. From the results obtained, only nine samples (28.1%) passed all the quality tests performed while five (15.6%), seven (21.9%) and 18 (56.3%) did not comply with pH, metronidazole content and assay specifications respectively. The results obtained demonstrate the existence of substandard metronidazole benzoate products in the market. This underscores the need for regular post market surveillance surveys and execution of appropriate regulatory actions.